Characterizing the Landscape of Service Provider Needs and Gaps in Services During the Canadian Youth Polysubstance Use Health Crisis. (June 2022) - Nairn, Stephanie A.; Hawke, Lisa D.; Isaacs, Jason Y.; Knight, Rod; Stewart, Sherry H.; Henderson, Joanna; Haines-Saah, Rebecca; Fast, Danya; Lam, Alice; Conrod, Patricia
ABSTRACT: Objectives: This study characterizes service provider needs, gaps, and problem areas in the provision of opioid-related services for young people ages 15 to 25 across Canada. Methods: A total of 154 service providers completed a 25-question survey that was comprised of closed-ended and open-ended questions about opioid-related services for youth. Descriptive statistics were generated using RStudio software and open-ended responses were coded using a content analysis approach. Results: The majority of participants were in the addiction and mental health (35.1%), prevention (18.2%), or housing/shelter (12.3%) sectors, provided services to youth in early adulthood demographic (19–21), and reported both illicit and prescription opioid use among the youth they served. The most common opioid-specific youth services provided were, referrals to other organizations (72.1%), individual therapy (64.9%), assessment/consultation (57.1%), and overdose prevention medication (Naloxone) (49.4%). Open-ended questions revealed needs for both a continuum of care and continuity of care, a lack of accessible and available services, organizational and financial barriers, and a lack of funding. Several respondents indicated that harm reduction services, counselling, and opioid agonist therapy were "well-developed" for youth. Conclusions: The majority of our respondents appear to be working in a polysubstance use context that includes both illicit and prescription opioid use by youth. Despite this, there was an emphasis on referrals to other organizations as the most common type of service for young people. This is a potentially interesting and alarming finding in the context of provider reports of fractured continuums of care and continuity of care for young people using opioids. There was some encouraging awareness of harm reduction and in particular Naloxone availability for young people, although as we noted, it is uncertain whether youth are actually provided with Naloxone and to what extent pharmacological and counselling therapies are made available and accessible (affordable) for them. Our results suggest that there is still a need for programs and initiatives for youth that target polysubstance use (including both illicit and prescription opioid use) for young people. Abstract : Objectifs: Cette étude décrit les besoins, les lacunes et les problématiques des fournisseurs de services dans la prestation de services liés à l'usage d'opioïdes chez les jeunes Canadiens âgés de 15 à 25 ans. Méthodologie: En tout, 154 fournisseurs de services ont répondu à un sondage de 25 questions fermées et ouvertes sur les services offerts aux jeunes consommateurs d'opioïdes. Des statistiques descriptives ont été générées à l'aide du logiciel RStudio et les réponses aux questions ouvertes ont été codées au moyen d'une stratégie d'analyse de contenu. Résultats: La majorité des participants étaient dans les secteurs des dépendances et de la santé mentale (35, 1%), de la prévention (18, 2%) ou de l'hébergement (12, 3%), ont fourni des services à de jeunes adultes (19 à 21 ans) et ont rapporté que ces jeunes consommaient des opioïdes illicites et d'ordonnance. Les services les plus souvent offerts aux jeunes consommateurs d'opioïdes étaient l'orientation vers d'autres organismes (72, 1%), la thérapie individuelle (64, 9%), l'évaluation et la consultation (57, 1%) et la distribution de naloxone en prévention des surdoses (49, 4%). Les questions ouvertes ont révélé la nécessité d'un continuum de soins et d'une continuité dans les soins, le manque de services accessibles et disponibles, des obstacles organisationnels et financiers ainsi qu'un manque de financement. Plusieurs répondants ont indiqué que les services de réduction des méfaits, de conseils et de traitement par agonistes opioïdes étaient « bien développés » pour les jeunes. Conclusions: La majorité des répondants semblent travailler dans un contexte de polyconsommation qui comprend l'usage d'opioïdes illicites et d'ordonnance chez les jeunes. Malgré tout, l'orientation vers d'autres organismes ressort comme étant le type de service le plus courant chez les jeunes. Cette constatation s'avère intéressante et potentiellement inquiétante à la lumière des rapports des fournisseurs sur les bris dans le continuum et la continuité des soins offerts aux jeunes consommateurs d'opioïdes. Le sondage indique une sensibilisation à la réduction des méfaits plutôt encourageante, surtout en ce qui concerne la disponibilité de la naloxone pour les jeunes, bien qu'on ne sache pas si les jeunes reçoivent effectivement la naloxone ni dans quelle mesure la pharmacothérapie et les conseils sont disponibles et accessibles (abordables) pour eux. Nos résultats indiquent qu'il existe encore un besoin de programmes et de projets axés sur la polyconsommation (y compris l'usage d'opioïdes illicites et d'ordonnance) chez les jeunes.